Toxic Metals, Chronic Diseases and Related Cancers - Satarug, Soisungwan (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Long-term exposure to environmental toxicants is estimated to account for 70-90% of the risks of acquiring chronic ailments. Presently, chronic kidney disease and infertility affect a significant proportion of the world population, while research data indicate that exposure to toxic metals may contribute to the looming statistics. Alarming evidence suggests that exposure to the heavy metal cadmium may affect every stage of life, and exposure in early life may determine susceptibility to certain diseases in adulthood. Prevention of these outcomes requires avoidance of further environmental contamination, minimization of exposure, and reduction of toxic metals in food crops to the lowest achievable levels.